Corporate Social Responsibility Disclosure and Financial Performance: A State Owned Enterprises Case Study - Susnaningsih Muat; Agung Prayogo (Sosial Budaya, 2018)
In today’s business environment, the maximization of shareholders wealth is not the only objective of a company. By engaging in the Corporate Social Responsibility (CSR) program, companies are also responsible for the interest of stakeholders and society at large. CSR disclosure is believed to improve financial performance. In State Owned Enterprises (SOE), however, the validity of this relationship has been called into question. In this paper, the main objective is to investigate the influence of CSR disclosure on financial performance in SOE. In relation to the measurement of financial performance, this study takes into account three indicators: Return on Equity (ROE), Earning Per Share (EPS), and Net Profit Margin (NPM). In this study, data from state owned enterprises, which were listed on the Indonesian Stock Exchange from the period of 2011 to 2015, were analyzed using simple regression method. The data used in this study took the form of financial and sustainability report issued by state owned enterprises. The results show that the disclosure of CSR has a significant positive effect on ROE. The CSR disclosure also has a significant positive effect on EPS. In contrast, the disclosure of CSR has no effect on NPM. In the context of State Owned Enterprises, the research demonstrates that there is positive relationship between CSR disclosure and financial performance. This paper contributes to our understanding of state owned enterprises in Indonesia; a research area which has to date been neglected by scholars.